The Effect of Hıgh Intensıty Narrow Fıeld Exercıses and Technıcal Traınıngs on Macro Mıneral Blood Parameters ın U14-U15 Football Players - Kenan Işildak, Gürhan Suna, Melisa Cansu Uzun (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The aim of this study is to examine the effects of 8-week ıntensity narrow field exercises and technical trainings on macro mineral blood parameters of U14-U15 football players. A total of 22 football players in the U14-U15 category participated in the study. Method: In the study, ıntensity narrow field exercises and technical trainings were performed 3 days a week for 8 weeks in the experimental group, and technical training was performed on the control group. A "Family Informed Consent (Consent) Form" was obtained from the parents of the athletes who wanted to participate in the study voluntarily. The study was prepared in accordance with the principles of the Declaration of Helsinki. Macro mineral blood parameters were taken for pre-test and post-test measurements in both groups. Appropriate SPSS statistical program was used in the analysis of the obtained data. The Shapiro-Wilk test was used to determine whether the data showed a normal distribution. Intragroup “Paired t test” to determine whether there is a difference before and after training; The difference between the groups was analyzed using the "Independent-t test". The significance level was evaluated according to the 0.05 significance level. Results: When the findings of the study were examined, there was a statistically significant difference in the macro mineral blood parameters of the experimental group before and after the training (p<0.05); no significant difference was found in the control group (p>0.05). As a result of the analysis of the comparison between the groups, there was a significant difference between the sodium post-test, potassium pre- and post-test results, while no significant difference was found in other measurement values. Conclusions: As a result, it has been determined that 8-week high ıntensity narrow field exercises applied to U14-U15 football players have effects on macro mineral blood parameters.